The Effect of Training and Motivation on ASN Performance in the Protocol Section of the General Bureau of the Bengkulu Province Secretariat - Harsen Jenizar; Karona Cahya Susena; Abdul Rahman (Penerbit Jurnal Indonesia, 2021)
The purpose of this study was to determine the effect of training and motivation on the performance of ASN in the Protocol Section of the General Bureau of the Bengkulu Province Secretariat. This study uses quantitative research, quantitative research is a process of finding knowledge that uses data in the form of numbers as a tool to analyze information about what you want to know. The value of the coefficient of determination or R square is 0.677. So the value of the coefficient of determination is 0.677 or equal to 67.7% This number means that the motivation variable (XI) and leadership (X2) simultaneously (together) affect the performance variable (Y) of 67.7%. While the rest (100% - 67.7% = 32.3%) is influenced by other variables outside this regression equation or variables not examined. This proves that the influence of motivation and leadership on performance in this study is quite large.